ANALISIS IMPLEMENTASI NILAI TOLERANSI MELALUI MATERI SIMBOL KEBERAGAMAN AGAMA PADA PESERTA DIDIK KELAS II SD NEGERI SRATEN 02 - Firdhaus Fimma Farhana; Hera Heru Sri Suryanti; Sarafuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of tolerance character values through the material on symbols of religious diversity and to identify the supporting and inhibiting factors in second-grade students at SD Negeri Sraten 02 in the 2024/2025 academic year. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that introducing religious symbols through visual media and habituating mutual respect in classroom activities effectively fosters students’ tolerance character. Teacher role modeling and school environment support serve as the main supporting factors, while differences in students’ understanding and limited learning media become the inhibiting factors. Overall, the implementation of religious diversity symbol material strengthens tolerance attitudes from an early age.